Geochemical effects of intra-layer hydrocarbon micro-migration in shale layers: a case study of the No. 5 shale layer of the No. Ⅲ sand group in the upper submember of the third member of the Paleogene Hetaoyuan Formation in the deep sag area of Biyang Sag, Nanxiang Basin - Dongmei ZHANG; Shuifu LI; Yanyan ZHANG; Peng SU; Changran ZHOU (Shiyou shiyan dizhi, 2025)
Hydrocarbon micro-migration within source rock layers is an important pathway for shale oil enrichment, and the resulting geochemical effects provide strong evidence for its occurrence. To verify the existence of hydrocarbon micro-migration in the deep sag area of the Biyang Sag of Nanxiang Basin and to investigate the enrichment mechanism of shale oil, the No. 5 shale layer of the No. Ⅲ sand group in the upper submember of the third member of the Paleogene Hetaoyuan Formation in wells BY1 and Cheng 2 was selected as the research object. By using geochemical analysis methods such as rock pyrolysis, extraction and chromatographic techniques, chromatography-mass spectrometry, and rock thin-section observation, the existence of hydrocarbon micro-migration within the shale layer in the study area and its resulting geochemical effects were revealed. The results indicated that, based on the relationship between pyrolytically desorbed hydrocarbon (S1) and total organic carbon (TOC), hydrocarbon micro-migration within the shale layer in the study area was divided into three types: weak hydrocarbon expulsion (type Ⅰ), strong hydrocarbon expulsion (type Ⅱ), and indigenous hydrocarbons (type Ⅲ), and their corresponding hydrocarbon expulsion intensities were quantitatively calculated. The geochemical characteristics of the three types of hydrocarbon micro-migration were as follows: type Ⅲ samples had the highest saturate/aromatic ratio, type Ⅱ samples had the lowest saturate/aromatic ratio, and type Ⅰ samples were in between. The ratio of n-alkane nC19 to methylphenanthrene (MP) showed a similar pattern. Additionally, rock thin-section observation further confirmed that type Ⅲ samples contained more reservoir space, allowing for indigenous hydrocarbon influx and storage. Type Ⅱ samples developed fractures, enabling smooth expulsion of oil and gas. Type Ⅰ samples had small pore and throat radii, low permeability, high capillary resistance, and undeveloped fractures, leading to poor expulsion capacity, which aligned with their resulting geochemical effects.